2014
DOI: 10.1007/s00125-014-3439-x
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific differences in diabetes prevention: a systematic review and meta-analysis

Abstract: Aims/hypothesis In people with prediabetes, lifestyle interventions and glucose-lowering medications are effective in preventing the progression to type 2 diabetes. It is unclear whether differences in treatment effects between men and women need to be taken into consideration when choosing a preventive strategy for an individual person. Methods We systematically searched PubMed, the Cochrane Library, EMBASE, CINAHL, Web of Science, and reference lists of pertinent review articles from 1980 to June 2013. We co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
2
6

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 66 publications
4
37
2
6
Order By: Relevance
“…25 27 29 37 One considered four primary studies and noted no gender differences in either 1-year or 2-year follow-up meta-analysis results 29. In contrast, analysis of data from 19 studies in a second review suggested that each 1-unit increase in study-level baseline percentage of men was associated with a 3% higher diabetes incidence 25.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…25 27 29 37 One considered four primary studies and noted no gender differences in either 1-year or 2-year follow-up meta-analysis results 29. In contrast, analysis of data from 19 studies in a second review suggested that each 1-unit increase in study-level baseline percentage of men was associated with a 3% higher diabetes incidence 25.…”
Section: Resultsmentioning
confidence: 99%
“…29 Review of pooled individual-level data from three primary studies suggested no impact of gender on weight outcomes,29 but again a study-level review suggested that each percentage increase in the proportion of male participants was borderline significantly associated with 0.05 kg net weight gain 25…”
Section: Resultsmentioning
confidence: 99%
“…We undertook the present analysis based on the observation from clinical lifestyle intervention trials that the improvement of glycaemia, which was achieved during the intervention, was relatively heterogeneous [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. Furthermore, several problems about successful translation of such interventions to clinical practice have been identified [29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…Conclusions/interpretation Stratification of individuals with prediabetes at baseline into a high-risk and a low-risk phenotype, based on corrected insulin secretion and insulin-resistant NAFLD, may help to determine the effectiveness of a lifestyle intervention to revert individuals to NGR. [1][2][3][4][5][6][7][8][9][10]. However, although this safe intervention is generally very effective at preventing diabetes, some people still develop the disease [1,3].…”
Section: Introductionmentioning
confidence: 99%
“…The US Diabetes Prevention Programme (DPP) found greater weight loss in men than women but the difference was not stated (1). A systematic review and meta-analysis on sex-specific differences in diabetes prevention found no evidence of sex differences in weight loss in people with prediabetes although weight loss at 3-years follow-up was greater in men than women (confidence intervals overlapped) (2). In a further systematic review of weight loss interventions, weight loss was found to be greater in men than in women in 80% of studies where a direct comparison was possible.…”
Section: Introductionmentioning
confidence: 99%